Comparison of Retrograde Intrarenal Surgery and Percutaneous Nephrolithotomy Methods For Management of Big- Sized Kidney Stones(? 4 cm): Single Center Retrospective Study - Karakoyunlu, Ahmet Nihat; Cakici, Mehmet Caglar; Sari, Sercan; Hepsen, Emre; Ozok, Hakki Ugur; Sagnak, Azmi Levent; Topaloglu, Hikmet; Senturk, Aykut Bugra; Ersoy, Hamit (Urology Journal, 2019)
Purpose: Management of ? 4 cm sized kidney stone is a rarely seen problem in urology. Few studies are present about this issue. Percutaneous nephrolithotomy(PNL), Retrograde Intrarenal Surgery(RIRS) and open surgery are the methods used in stone management. In our study we aimed to compare RIRS and PNL in the management of ? 4 cm sized kidney stones. Materials and methods: Among patients who had undergone RIRS and PNL in D?skap? Y?ld?r?m Beyaz?t Training and Research Hospital, 94 patients who had ? 4 cm sized kidney stones were included our study. The demographic, intraoperative and postoperative data of these patients and complications were evaluated retrospectively. Results: 94 patients (67 PNL, 27 RIRS) were in the study. Stone laterality, urinary anomaly and gender were similar in two groups.(Group PNL(P) and Group RIRS(R)) Stone number were 2.55 ± 1.44 and 2.78 ± 1.42 in Group P and R, respectively. Stone size were 47.06 ± 7.02 and 46.41 ± 6.00 mm. in Group P and R, respectively. The differences between two groups were not statistically significant.(P > .05) In Group P scopy time, hospital stay and stone free rate were higher and operation time was lower than Group R. And the difference was statistically significant(P < .05). Conclusions: As a result, PNL is an effective method and operation time is lower than RIRS. Also a second operation for JJ stent taking is lower in PNL . RIRS is a safe method. RIRS has less complications and hospitalization time. They are feasible in treatment of ? 4 cm sized kidney stones.